Abordagem Leader: uma aproximação com o programa territórios da cidadania - Rodrigues, Suelen de Leal (2014)
Analyzing evidences of the LEADER approach in the Territories of Citizenship Program consists in the immediate objective of this paper. Considering the current context in which the territorial approach takes on the challenge of promoting a less excluding development, the deepening of discussions and experiences highlighted in national and international scope can add elements for analysis and creation of proposals for a more efficient development. Methodologically, a qualitative analysis of bibliographic data and interviews involving focal subject types was performed. In the analysis performed it was possible to understand that the policy of territorial approach is necessary, but it has structural implications that hinder the work of those who should mediate and sensitize the most excluded social groups. Therefore, so that there is an effective policy it would be necessary to create participatory and emancipatory models able to produce structural changes.